The strategic managing of human resources - Leopold, John W.; Harris, Lynette; Watson, Tony J. (Prentice Hall., 2005)
Starting from the premise that managing human resources strategically is crucial for long term organizational success, this work is essential reading for both future line managers as well as specialist Human Resource Managers